2006
DOI: 10.1111/j.1365-2796.2006.01631.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory symptoms as predictors of all‐cause mortality in an urban community: a 30‐year follow‐up

Abstract: Abstract. Frostad A, Søyseth V, Andersen A, Gulsvik A (Cancer Registry of Norway, Oslo; Akershus University Hospital, Lorenskog; and University of Bergen, Bergen; Norway) Respiratory symptoms as predictors of all-cause mortality in an urban community: a 30-year follow-up. J Intern Med 2006; 259: 520-529.Objective. We investigated the relationship between respiratory symptoms and mortality from all causes in a large Norwegian population. We also examined mortality during separate periods of follow-up. Design. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
54
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 27 publications
9
54
0
5
Order By: Relevance
“…Beyond the interest for cardiovascular diseases, this long observation prompted interest in allcause mortality and its determinants. A few studies have reported long-term analyses on all-cause deaths but rarely reaching 40-year of follow-up [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the interest for cardiovascular diseases, this long observation prompted interest in allcause mortality and its determinants. A few studies have reported long-term analyses on all-cause deaths but rarely reaching 40-year of follow-up [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous studies suggest that chest symptoms are considered as important predictors of all-cause mortality (1)(2)(3)(4) …”
Section: Introductionmentioning
confidence: 99%
“…There is a robust series of studies demonstrating that Chronic Bronchitis is associated with increased morbidity and mortality. It is an independent risk factor for all cause mortality both in COPD (38), and in subjects with normal lung function, even when smoking has been accounted for (38)(39)(40). The overall ten year mortality following a diagnosis of chronic bronchitis is 50%, with respiratory failure following an acute exacerbation being the most frequent terminal event (41).…”
Section: Sputum Characteristicsmentioning
confidence: 99%